Responding to Interprofessional Microaggressions: Bystander Training-A Virtual Simulation Curriculum for Internal Medicine Residents - Radha Govindraj; Dhanesh D. Binda; Angelique C. Harris; Sonia Ananthakrishnan; Meghan E. McGrath; Wendy Kuohung; Tun-Yi Hsu; Jennifer Siegel; Gopal Yadavalli (Association of American Medical Colleges, 2024)
Introduction Literature demonstrates the detrimental impact of discrimination and microaggressions at personal and institutional levels in the health care workplace. Residents in our program requested curricula to help with addressing manifestations of bias. In response, we designed and implemented an adaptable and reproducible 4-hour virtual simulation session aimed at helping residents identify and constructively respond to microaggressions. Methods This curriculum, influenced by a preceding needs assessment, was delivered to 68 senior internal medicine residents. It began with a didactic overview to establish foundational knowledge of bias. This was followed by a workshop focused on strategies to address microaggressions. The session culminated with skills practice in a virtual simulation activity where learners addressed microaggressions as bystanders in realistic case scenarios employing simulated participants. We administered pre- and postevaluation individual key-linked surveys assessing learner confidence in responding to microaggressions. Results A total of 68 residents participated in the curriculum over two academic years, 27 of whom provided complete data for analysis. Overall, there was a statistically significant increase in learner confidence identifying microaggressions. As both a bystander and target/recipient of microaggressions, there were statistically significant increases in learner confidence addressing gender-based microaggressions, race-based microaggressions, and microaggressions reflecting other types of bias. Furthermore, there were statistically significant increases in learner confidence addressing microaggressions in low-acuity contexts, high-acuity contexts, across interprofessional disciplines, with a supervisor, and with a supervisee. Discussion Our virtual experiential curriculum on responding to microaggressions can help increase learner confidence in addressing microaggressions.